2017
DOI: 10.3168/jds.2016-11313
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear genetic relationships between type traits and productive life in US dairy goats

Abstract: Linear or nonlinear genetic relationships between productive life and functional productive life at 72 mo, with final score (SCO), stature, strength, dairyness (DAI), teat diameter, rear legs (side view), rump angle, rump width (RUW), fore udder attachment (FUA), rear udder height, rear udder arch, udder depth (UDD), suspensory ligament (SUS), and teat placement, as well as heritabilities and correlations were estimated from multibreed US dairy goat records. Productive life was defined as the total days in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 47 publications
(86 reference statements)
3
27
5
1
Order By: Relevance
“…The averages and standard deviations obtained for type traits in US goats [22] were not very different than those estimated for some traits in this study. Averages for FIS, FUA and UDD were similar [22]. Coefficients of variation for MILK, FAT and PROTEIN are within the range of estimates for these traits in other US dairy goat populations [11].…”
Section: A C C E P T E Dcontrasting
confidence: 74%
See 1 more Smart Citation
“…The averages and standard deviations obtained for type traits in US goats [22] were not very different than those estimated for some traits in this study. Averages for FIS, FUA and UDD were similar [22]. Coefficients of variation for MILK, FAT and PROTEIN are within the range of estimates for these traits in other US dairy goat populations [11].…”
Section: A C C E P T E Dcontrasting
confidence: 74%
“…The averages for fat and protein content in this data were higher compared to other breeds [3,20,21]. The averages and standard deviations obtained for type traits in US goats [22] were not very different than those estimated for some traits in this study. Averages for FIS, FUA and UDD were similar [22].…”
Section: A C C E P T E Dcontrasting
confidence: 55%
“…Quantitative trait loci for traits such as birth and weaning weight (Mohammad Abadi et al, 2009;Visser et al, 2013), hair fiber characteristics (Cano et al, 2007;Visser et al, 2011), growth (Mohammad Abadi et al, 2009), body conformation (Marrube et al, 2007), parasite resistance (Bolormaa et al, 2010;De La Chevrotière et al, 2012), milk traits (Roldán et al, 2008), and α S1 -casein (Sacchi et al, 2005;Hayes et al, 2006;Dagnachew et al, 2011) have been identified in goats using microsatellite markers. With the availability of the Illumina Caprine 50K BeadChip (Illumina Inc., San Diego, CA;Tosser-Klopp et al, 2012, 2014, it is now possible to perform genome-wide scans in goats Genome-wide association study of conformation and milk yield in mixed-breed dairy goats with much greater resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, feet and leg conformation has been genetically linked to claw disorders (van der Waaij et al, 2005), although there is evidence that animals with good udder conformation are less sensitive to high yields than those with poor udder conformation (Philipsson and Lindhé, 2003). In dairy goats, there is evidence of genetic correlations with production traits such as milk yield (McLaren et al, 2016) and productive life, as well as functional productive life (Castañeda-Bustos et al, 2017). Udder and teat conformation have also been linked with elevated SCC and clinical mastitis (Rupp and Boichard, 1999;Rupp et al, 2011;Huntley et al, 2012) as well as milking speed (Sewalem et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Heritability estimates for daily milk yield and milk fat and protein content were 0.26 and 0.24 to 0.27 (Table 1), respectively [24]. Generally, biometric studies have switched from classical studies on heritabilities and genetic correlations of milk and component yields to studies involving longevity [25] or incorporating genomic information into standard genetic evaluations [26].…”
Section: Biometricsmentioning
confidence: 99%